2021
DOI: 10.1101/2021.07.21.453275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Raptor downregulation rescues neuronal phenotypes in mouse models of Tuberous Sclerosis Complex

Abstract: Tuberous Sclerosis Complex (TSC) is a neurodevelopmental disorder caused by mutations in the TSC1 or TSC2 genes, which encode proteins that negatively regulate mTOR complex 1 (mTORC1) signaling. Current treatment strategies focus on mTOR inhibition with rapamycin and its derivatives. While effective at improving some aspects of TSC, chronic rapamycin inhibits both mTORC1 and mTORC2 and is associated with systemic side-effects. It is currently unknown which mTOR complex is most relevant for TSC-related brain ph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…We have previously shown that Cre-dependent deletion of Rictor reduces p-473 Akt levels in cultured hippocampal neurons, indicative of suppressed mTORC2 activity ( Karalis et al, 2021b ). Due to technical limitations of the antibody, we were not able to assess p-473 at the level of individual neurons in brain sections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that Cre-dependent deletion of Rictor reduces p-473 Akt levels in cultured hippocampal neurons, indicative of suppressed mTORC2 activity ( Karalis et al, 2021b ). Due to technical limitations of the antibody, we were not able to assess p-473 at the level of individual neurons in brain sections.…”
Section: Resultsmentioning
confidence: 99%
“…In mature neurons, mTOR controls neuronal morphology, physiology, and synaptic properties ( Costa-Mattioli and Monteggia, 2013 ; Hoeffer and Klann, 2010 ; Switon et al, 2017 ). Consequently, dysregulation of mTOR signaling has a profound impact on nervous system function and several neurodevelopmental, psychiatric and neurodegenerative disorders are directly caused by or associated with altered mTOR activity ( Costa-Mattioli and Monteggia, 2013 ; Karalis et al, 2021b ; Lipton and Sahin, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation